2022
DOI: 10.1177/14673584221126798
|View full text |Cite
|
Sign up to set email alerts
|

Destination brand image and destination brand choice in the context of health crisis: Scale development

Abstract: Several recent destination crises have brought difficult challenges to the world’s travel, hospitality, and tourism activities. We explore how the brand image of a tourist destination is influenced by health crises, specifically within the context of the COVID-19 pandemic. We conducted interviews and online data collection in China. Exploratory factor analysis and confirmatory factor analysis were conducted to develop, purify, and verify scale items that measure perceived destination brand image, destination b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…The review identified recurrent theories and conceptual frameworks under which the hypotheses were developed. Examples of some well-known theories employed are Mehrabian and Russell’s (1974) stimulus-organism-response (S-O-R) in Koç et al (2022) , Majeed et al (2022) , and Nie et al (2022) , Rogers’ (1975) protection motivation theory (PMT) in Rather (2021) and Cambra-Fierro et al (2022) , or Ajzen’s (1991) theory of planned behavior (TPB) in Torabi et al (2022) , adding to the integration of research findings with higher-level theoretical explanations ( Hunt, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review identified recurrent theories and conceptual frameworks under which the hypotheses were developed. Examples of some well-known theories employed are Mehrabian and Russell’s (1974) stimulus-organism-response (S-O-R) in Koç et al (2022) , Majeed et al (2022) , and Nie et al (2022) , Rogers’ (1975) protection motivation theory (PMT) in Rather (2021) and Cambra-Fierro et al (2022) , or Ajzen’s (1991) theory of planned behavior (TPB) in Torabi et al (2022) , adding to the integration of research findings with higher-level theoretical explanations ( Hunt, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another special case of loyalty operationalization was in the research by Huete-Alcocer and Hernandez-Rojas (2022) , who found cuisine-based destination loyalty formed by the overall image of the destination (β = 0.219), its local gastronomy (β = 0.251), and satisfaction with restaurants (β = 0.403), all of which are in turn predicted by COVID-19 safety measures at restaurants. Finally, Majeed et al (2022) developed the destination brand image and tourist behavior (DBITB) scale which included a dimension corresponding to destination choice/loyalty, but no prediction of external constructs was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperconnectivity has fueled the unprecedented growth of OBCs, in which consumers interact with brands, share ideas and make informed brand selections, for both new and established brands, such as Jeep and Sephora, (Swaminathan et al , 2020). Previous studies have examined the significant positive associations between online brand communities as a predictor variable and consumer response in terms of inspiration (Cao et al , 2021); inspired customers develop brand engagement, which impacts brand choice (Majeed et al , 2022b) and can arguably be linked to OHBS.…”
Section: Touchpoints (Channels) Of Online Hyperconnected Brand Selectionmentioning
confidence: 99%
“…The stimulus-organism-response (SOR) framework of Mehrabian and Russell (1974) is important to understanding consumer experience and behavior in the online hyperconnected environment (see Cao and Sun, 2018; Zhang et al , 2014). Previous studies have used it to show that external stimuli (S) have the power to shape behavior (R) via cognitive organism (O) state (Majeed et al , 2022b). In this paper, the predictors of OHBS (see Figure 1) are external stimuli (O); the development of perceived OHBE, FTC and FTE are organism (O); and perceived well-being and behavioral intention are response (R) in terms of the SOR framework.…”
Section: Conceptual Framework and Theoretical Viabilitymentioning
confidence: 99%
“…Some researchers view engagement in a one-dimensional way [39][40][41] (e.g., clicking on online content). Other scholars argue that brand engagement should be viewed instead as a manifestation of engagement rather than an operational definition of this concept [42].…”
Section: Dimensionality and Measurement Of Engagementmentioning
confidence: 99%